Microregional convergence through social innovation - Mariann Veresné Somosi; Krisztina Varga (Theory, Methodology, Practice, 2021)
The national and international literature pays increasing attention to the research of social innovation and its impacts. Among the areas to be examined, we deal with the issues of measurability within the framework of the study. The conceptualization of social innovation, the determination of the logic of the social innovation process and the definiton of its measurement levels, and modeling based on empirical research are relevant challenges. However, the different sources dealing with the topic examine these issues in a different approach. The purpose of the study is to investigate the social innovation endeavours of a district to be developed by a complex program. Nyírbátor District includes disadvantaged settlements that are facing numerous problems due to their peripheral position. The challenges of the area (migration, ageing, unemployment and scarce financial resources) mean doubly disadvantageous stigmatization for these settlements. On the one hand, they mean an external negative judgment, and on the other hand, an internal stigmatization processes of local inhabitants, which require the exact identification of local needs and the involvement of the inhabitants in decisions. One of the tools of such initiatives can be social innovation, and also the support of social innovation endeavours. Within the framework of the research, we examine social innovation as a process of creative cooperation, during which we pay special attention to the analysis of social initiatives supported by local governments. The social innovation endeavours presented in the framework of the study are multi-stakeholder initiatives based on the involvement of the local population.. Their good practice analysis makes it possible to map the process of social innovation. The purpose of this study is to present the points of focus that serve as potential activating factors for the endeavours in the case of Nyírbátor District. The examined cases play a significant role in managing the unfavourable processes of the area, and their adaptation as best practices can support the process of catching up. The study also defines the main sets of criteria which, in addition to providing a structured record of individual case studies, help to compare good practices.